2013
DOI: 10.1371/journal.pone.0077017
|View full text |Cite
|
Sign up to set email alerts
|

Mosquitoes of Western Yunnan Province, China: Seasonal Abundance, Diversity, and Arbovirus Associations

Abstract: ObjectiveThe western borderland between Yunnan Province, China, and Myanmar is characterized by a climate that facilitates year-round production of mosquitoes. Numerous mosquito-transmitted viruses, including Japanese encephalitis virus circulate in this area. This project was to describe seasonal patterns in mosquito species abundance and arbovirus activity in the mosquito populations.MethodsMosquitoes were collected in Mangshi and Ruili cities of Dehong Prefecture near the border of China and Burma in Yunnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 32 publications
(33 reference statements)
0
23
0
Order By: Relevance
“…Armigeres ( Armigeres ) subalbatus is a species complex of zoophilic mosquitoes belonging to the genus Armigeres , which is the least studied genus of mosquitoes captured during this study with regard to public health [ 36 , 49 , 50 ]. It is a natural vector for filarial worms of livestock, which causes filariasis in humans [ 36 , 50 ]. This species has also been found at a low density and carrying virus in Yunnan, China [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Armigeres ( Armigeres ) subalbatus is a species complex of zoophilic mosquitoes belonging to the genus Armigeres , which is the least studied genus of mosquitoes captured during this study with regard to public health [ 36 , 49 , 50 ]. It is a natural vector for filarial worms of livestock, which causes filariasis in humans [ 36 , 50 ]. This species has also been found at a low density and carrying virus in Yunnan, China [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a natural vector for filarial worms of livestock, which causes filariasis in humans [ 36 , 50 ]. This species has also been found at a low density and carrying virus in Yunnan, China [ 50 ]. Moreover, a study in central China found that Ar.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of CDC-LT with dry ice was most effective for trapping of Cx. quinquefasciatus when compared with UV light traps and gravid traps in China [ 33 ]. This effect was not observed in the present study but this may be attributable to the low numbers of Cx.…”
Section: Discussionmentioning
confidence: 99%
“…sinensis and Cx. pipiens , which are also competent vectors for several zoonotic viruses important to public health (Carlson, Suchman, & Buchatsky, ; Ng et al, ; Ren, Hoiczyk, & Rasgon, ; Shi et al, ; Zhai et al, ; Zhang et al, ). Although it is still not clear how MDVs cause larval mortality, it appears that MDVs increase cellular apoptosis which may be the reason for this mechanism (Roekring & Smith, ).…”
Section: Resultsmentioning
confidence: 99%